The complete mitochondrial genome of Holothuria atra (Holothuriida: Holothuriidae: Holothuria) and its structural characteristics - Jinjin Wang; Jianlong Ge; Meijie Liao; Bin Li; Xiaojun Rong; Yingeng Wang; Aijun Cui; Xiaodong Bian; Mingliang Sun; Qingyu Zhang (PLoS ONE, 2026)
Sea cucumbers, as typical representatives of deep-sea benthic animals, possess significant scientific and economic importance. This investigation examined the genomic structural characteristics and genetic evolutionary relationships of Holothuria atra through the analysis of its complete mitochondrial genome. The findings indicated that the total length of the mitochondrial genome of the H. atra specimen was 15,788 bp, encompassing seven NADH genes, three cox genes, two ATP genes, and one cob gene. Additionally, two rRNAs and 22 tRNAs were identified. The entire sequence contained a total of 18 non-coding regions and seven overlapping gene regions, with the combined A + T content reaching 59.2%. The lengths of the 22 tRNAs ranged from 62 to 72 base pairs, and their cloverleaf secondary structures were predicted. Regarding codon usage, the PCGs within the mitochondrial genome of H. atra utilized 61 codons, encoding information for 20 amino acids. The most abundantly encoded amino acid in the mitochondrial genome of H. atra is leucine (Leu), representing 16.58%, while cysteine (Cys) is the least represented, accounting for 1.03%. Codons with higher usage frequencies include AGA (Ser 1), CUA (Leu 1), and CCA (Pro), whereas those with comparatively lower frequencies are GCG (Ala), CCG (Pro), and AGG (Ser 1). Evolutionary analysis revealed that H. atra is most closely related to Holothuria polii . By comparing the mitochondrial genomic sequences of 19 species within the class Holothuroidea, it was observed that eight mitochondrial sequences are shared among these species. This study provides valuable data supporting genetic evolutionary research and the development and utilization of H. atra resources within the Kiribati region.